An interactive design change methodology using a BIM-based Virtual Reality and Augmented Reality. (1st June 2023) - Panya, David Stephen; Kim, Taehoon; Choo, Seungyeon
Abstract: Changes in design and construction constitute variations from the original design prepared by a design team and are inevitable. Despite the fact that rework has been identified as having adverse effects on performance, there have been limited studies on how to mitigate rework in design changes. Despite improving change management, Building Information Modeling (BIM) is insufficient in mitigating rework. However, the convergence of the capabilities of BIM, Virtual Reality (VR), and Augmented Reality (AR) are integrated solutions to reduce the impact of rework in design change. In this research, we improve the requirements for reworking design changes, which include redesign, information flow, and delivery for users with no experience with BIM. For interactive design change with BIM in VR and AR, the proposed methodology integrates BIM, as-built data from web sources, and VR and AR functions using game engines and programming. In VR and AR, BIM objects are used to create multiple variants that are matched with BIM databases that provide options for design changes. The interactive design change platform is validated in a VR and AR environment and presented multiple design change options for wall elements based on a set required change factor of a building project. This paper highlights the need for a change platform that reduces the rework of design changes in BIM through VR and AR in three main areas redesign, maintaining the flow of information and delivery of solutions for design changes. The VR and AR proposed solution to design change improves rework collaboration and communication among stakeholders of a building project. Highlights: Integrating BIM, VR and AR reduces the rework of design changes. A VR and AR library is developed for real-time design change that relay as-built information. Collaboration is increased in design changes by presenting rework options from a VR and AR library.